Gender Responsive Pedagogy in Thematic Learning in Elementary Schools - Mochamad Nasrul Amin; Kemil wachidah (Mimbar Ilmu, 2023)
Gender-responsive thematic learning still needs to be found in elementary schools. Gender bias is still found in some student teaching materials. It can trigger the emergence of a mindset in students that will continue to be carried into adulthood, resulting in gender inequality. This study aims to analyze gender-responsive thematic learning in elementary schools. This research is a case study, with the subjects involved, namely 2 class V teachers. Data collection techniques used in this study were interviews, observation, and documentation, with research instruments in the form of observation and interview guidelines. Data analysis techniques are carried out through several stages, namely data collection, data reduction, data display, and making conclusions. The results of this study indicate that teachers have a very important role in implementing gender-responsive thematic learning in elementary schools. Gender-responsive thematic learning in elementary schools is carried out by determining learning objectives, making learning tools like lesson plans and teaching materials free from gender bias, and conducting fair and objective assessments. Classroom management is carried out by providing the same facilities to students in the learning process, not to benefit or harm one gender.